The Challenge of Enforcement in Securities Markets : Mission Impossible? - Carvajal, Ana (IMF Working Papers; Working Paper, 2009)
Weaknesses in the enforcement of regulation have been targeted by the G-20 as a priority concern for reform. But enforcement efforts in securities markets have proven difficult and uneven. The recent scandal in the United States, wherein a Ponzi scheme orchestrated by Bernard Madoff went undetected by the U.S. authorities for more than two decades, has once again highlighted the importance of effective enforcement of securities regulation, as well as the challenges that securities regulators around the world face in implementing credible enforcement programs. While in many instances it is individuals who bear the losses, we show that noncompliance with securities law can have serious system-wide impact and that the credibility of the system as a whole rests on the existence of effective discipline-the probability of real consequences for failure to obey the law. This paper explores the elements of enforcement, why it is so challenging, why it is important, and whether its effects can be measured. Through an analysis of the data gathered in the World Bank/IMF Financial Sector Assessment Program (FSAP), the paper examines how enforcement is being carried out around the world and draws conclusions regarding how countries are meeting the challenge of effective enforcement.